MENYINGKAP BENIH-BENIH INTOLERANSI DALAM BERAGAMA MELALUI FILSAFAT ATEISME LUDWIG FEUERBACH - Antono Wahyudi (Sanjiwani: Jurnal Filsafat, 2023)
Atheism is often seen as a paradigm which contradicts to a religion, in which the discourse of tolerance and intolerance is not seen as compatible for it. Is it possible that the seeds of intolerance can be exposed by the atheism paradigm approach? Thus, practically-pragmatically, is it important to understand the view of atheism in order to create a tolerant awareness? This paper aims to reveal the seeds of intolerance from Ludwig Feuerbach's philosophy of atheism. With the method of qualitative and library research on his magnum opus as well as several philosophical-analytical notes from commentators, the main points of Feuerbach's ideas able to reveal the seeds of intolerance through the philosophy of consciousness, materialism and idealism, the theory of projection as well as the issue of alienation. As a result, human values can be drawn as a conclusion from Feuerbach's atheistic philosophical system. In addition, the paradigm of atheism is an important discourse to study as an effort to complete the idea of tolerance while at the same time narrowing the space for intolerance to grow and spread more widely.